2004
DOI: 10.1021/bi0363073
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Determinants of Heritable Vitamin E Deficiency

Abstract: Tocopherol transfer protein (TTP) is a key regulator of vitamin E homeostasis. TTP is presumed to function by transporting the hydrophobic vitamin between cellular compartments, thus facilitating its secretion to the extracellular space. Indeed, recombinant TTP demonstrates marked ability to facilitate tocopherol transfer between lipid bilayers. We report the biochemical characterization of six missense mutations TTP(1) that are found in human AVED patients. We expressed the H101Q, A120T, R192H, R59W, E141K, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
41
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 37 publications
4
41
0
Order By: Relevance
“…These observations confirm previous reports that demonstrated a ca. 5-fold lower affinity of this mutant to tocopherol, as compared to wild-type TTP (25). Moreover, these data illustrate the utility of NBD-TOH for the detection of subtle perturbations to TTP's ligand binding pocket.…”
Section: Affinity Of Nbd-toh To Ttpmentioning
confidence: 65%
See 3 more Smart Citations
“…These observations confirm previous reports that demonstrated a ca. 5-fold lower affinity of this mutant to tocopherol, as compared to wild-type TTP (25). Moreover, these data illustrate the utility of NBD-TOH for the detection of subtle perturbations to TTP's ligand binding pocket.…”
Section: Affinity Of Nbd-toh To Ttpmentioning
confidence: 65%
“…We have previously shown that several TTP variants associated with the AVED pathology are impaired in facilitating vesicle-to-vesicle tocopherol transfer in vitro (25). We asked whether we could detect analogous differences in the kinetics of the isolated partial reaction (tocopherol dissociation from the bilayer).…”
Section: Kinetic Resolution Of Ttp's Ligand Transfer Activitymentioning
confidence: 96%
See 2 more Smart Citations
“…In humans, mutations in the TTPA gene cause systemic vitamin E deficiency accompanied by neurological compromise, primarily spinocerebellar ataxia (10 -17). Patients afflicted with this disorder (ataxia with vitamin E deficiency; OMIM 277460) present with debilitating neurodegeneration, the severity of which depends on the specific mutation's effect on TTP's biochemical activity (18,19). Lifelong vitamin E supplementation can delay or reverse disease progression, especially when patients are treated in earlier stages (20,21).…”
mentioning
confidence: 99%